Organic Production Systems: What the Biological Cell Can Teach Us About Manufacturing - DEMEESTER, Lieven (Institutional Knowledge at Singapore Management University, 2004)
Biological cells run complicated and sophisticated production systems. The study of the cell's production technology provides us with insights that are potentially useful in industrial manufacturing. When comparing cell metabolism with manufacturing techniques in industry, we find some striking commonalities, but also some important differences. Like today's well-run factories, the cell operates a very lean production system, assures quality at the source, and uses component commonality to simplify production. While we can certainly learn from how the cell accomplishes these parallels, it is even more interesting to look at how the cell operates differently. In biological cells, all products and machines are built from a small set of common building blocks that circulate in local recycling loops. Production equipment is added, removed, or renewed instantly when needed. The cell's manufacturing unit is highly autonomous and reacts quickly to a wide range of changes in the local environment. Although this organic production system is very different from existing manufacturing systems, some of its principles are applicable to manufacturing, and indeed, a few can even be seen emerging today. Thus, the organic production system can be viewed as a possible scenario for the future of manufacturing.